2009
DOI: 10.1186/1476-511x-8-29
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profile in oral submucous fibrosis

Abstract: Background: Changes in lipid profile have long been associated with malignancies as lipids play a key role in maintenance of cell integrity. This study evaluated the alterations in extended lipid profile in untreated patients of oral submucous fibrosis (OSMF) and studied the correlation between lipid levels with tobacco consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
24
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 19 publications
6
24
3
Order By: Relevance
“…TC and LDL-C values were higher in cases than in controls, while HDL-C value was lower in cases than in controls; however the difference in both were not significant. These results were comparable to the studies of lipid profile with submucosal fibrosis and breast cancer by Mehrotra et al (2009);Dabrowa et al (2011);Laisupasin et al (2013). Cconsidering varying grades of cervical cancer, TC and LDL-C increased from WDSCC to PDSCC but was not statistically significant.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…TC and LDL-C values were higher in cases than in controls, while HDL-C value was lower in cases than in controls; however the difference in both were not significant. These results were comparable to the studies of lipid profile with submucosal fibrosis and breast cancer by Mehrotra et al (2009);Dabrowa et al (2011);Laisupasin et al (2013). Cconsidering varying grades of cervical cancer, TC and LDL-C increased from WDSCC to PDSCC but was not statistically significant.…”
Section: Discussionsupporting
confidence: 80%
“…Hence it was concluded that estimation of lipid profile can be a good marker for increased cell turnover (Nayak et al, 2000). In a study of lipid profile and submucosal fibrosis, significant decrease in TC and HDL-C and significant increase in LDL-C and TG was observed (Mehrotra et al, 2009). In another study TC, TG and HDL-C showed significant decrease in oral cancer patients compared with controls with insignificant values of LDL-C.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations